Are hemoglobin and volume oxygen maximum (vo2max) relevant each other? - Isti Dwi Puspita Wati (Journal Sport Area, 2021)
The support for recording achievements in sports achievements, two of which are the ability to enter oxygen (O2) into the lungs and further the ability to take up this oxygen so that it can be utilized in the process of providing energy. The second function of O2 is to transport carbon dioxide (CO2) through respiration. These two processes are carried out simultaneously at least between the respiratory cycle and its close relationship with hemoglobin. Hemoglobin is part of the blood which has a function to bind O2 and CO2 at the end in the process of respiration. The purpose of this study was to determine evidence of a relationship between HB and VO2max. This research is a descriptive correlational study. Samples are sports athletes who are preparing for Pre PAPUA. The number of samples was 83 athletes in the game group consisting of sand volleyball (6), badminton (17), Petanque (12), table tennis (13), and Futsal (35). Measurement of VO2max was done by using the Bleep test and HB with the Hb test. Based on Kendall's tau non-parametric analysis, it is found that HB and VO2max are sufficiently correlated, so it is not certain that the higher the HB the higher the VO2max, although in the process of supplying energy these two variables are mutually supportive and relate.